Encountering Asylum Seekers: An Ethic of Fear or Faith? - Snyder, Susanna (Studies in Christian ethics, 2011)
Asylum is a contentious public and political issue and people seeking asylum are often targets of fear and hostility. This article presents an ethical challenge to churches aiming to support asylum seekers in the UK. Through an exploration of two contrasting strands in the biblical tradition relating to the ‘stranger’—one rooted in an ‘ecology of fear’ and another rooted in an ‘ecology of faith’—it argues that as well as practising positive encounters with newcomers, Christians need to understand and engage with public hostility.